The Influence of TikTok Ads and Consumer Behavior on Purchasing Decisions at Sari Kusuma Eye Therapy Services 99 - Abdullah, Hamzah Ali; Fabrianto, Luky (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
This study aims to analyze the influence of TikTok Ads and consumer behavior on purchasing decisions in Sari Kusuma 99 eye therapy services. The main problem raised is the still limited understanding of the effectiveness of digital marketing through the TikTok platform and how consumer behavior plays a role in the purchasing decision-making process in healthcare services. This study uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to respondents who had seen or been exposed to Sari Kusuma 99 TikTok Ads. The data analysis technique was carried out using Structural Equation Modeling Partial Least Square (SEM-PLS) with the help of the SmartPLS version 3 application to obtain more accurate and comprehensive results. The results show that TikTok Ads and consumer behavior simultaneously have a significant influence on purchasing decisions, with an R Square value of 83.3%. Consumer behavior was found to be the most dominant factor in influencing purchasing decisions, while TikTok Ads also have a significant influence although at a more moderate level. These findings emphasize the importance of integrating digital marketing strategies with an understanding of consumer behavior to increase promotional effectiveness while driving purchasing decisions in the digital business era. This research is expected to contribute to the development of digital marketing theory and become a practical reference for healthcare companies in designing more effective, targeted, and highly competitive promotional strategies